Impact of Adult Scoliosis on Roussouly Sagittal Shape Classification. Issue 4 (15th February 2019) - Pizones, Javier; Martin, Montserrat Baldan; Perez-Grueso, Francisco Javier Sánchez; Yilgor, Caglar; Vila-Casademunt, Alba; Serra-Burriel, Miquel; Obeid, Ibrahim; Alanay, Ahmet; Acaroglu, Emre R.; Pellisé, Ferran
Abstract : Study Design: A retrospective analysis of data collected prospectively in an adult spine deformity multicenter database. Objective: The aim of this study was to determine the impact of adult scoliosis (AS) on the type of Roussouly sagittal shape in terms of classification applicability, scoliosis modification of a patient theoretical sagittal shape, and coronal-sagittal deformity associations. Summary of Background Data: Roussouly described a four-type sagittal shape classification in healthy individuals, which has been also applied to patients with degenerative spinal disease. However, it remains uncertain if its principles can be applied to AS patients. Methods: AS patients recorded in a prospective multicenter database of adult spinal deformity were included. Preoperative sagittal radiographs were analyzed using the KEOPS software to measure pelvic parameters, global sagittal alignment, and the various criteria used for the Roussouly classification. The different sagittal shape types were compared using the Chi-square and McNemars tests, and analysis of variance with Bonferroni correction. Results: The classification was applicable to all of the 190 analyzed AS patients. In addition to Roussouly criteria, two parameters helped differentiate the different shapes: T10-L2 angle (24° ± 19 type-1; 14° ± 15 type-2; 3° ± 15 type-3; 0.4° ± 14 type-4; P  < 0.001), and lordosis distribution index (90% ± 17 type-1; 83% ± 16 type-2; 73% ± 21 type-3; 63% ± 16 type-4; P  < 0.001). AS changed the theoretical shape in 34% of the patients ( P  < 0.001). Curve etiology and curve pattern were not associated with any particular type of sagittal shape ( P  > 0.05). Type-1 was associated with older patients ( P  = 0.02), degenerative curves ( P  = 0.02), and greater PI-LL mismatch ( P  = 0.012). Types 3 to 4 were associated with younger age and idiopathic etiology ( P  < 0.001). Conclusion: Roussouly four-type sagittal shape classification could be applied to AS patients. AS modified the theoretical type in one of every three patients. No particular association was found between the sagittal types and specific coronal deformities. Sagittal shape recognition in patients with AS will help restore the appropriate theoretical shape through surgery, which can eventually lead to better surgical outcomes Level of Evidence: 2 Abstract : Roussouly's sagittal shape classification could be applied to 190 patients with adult scoliosis. Adult scoliosis modified the theoretical shape in 1 of every 3 patients. Although no particular association was found between sagittal types and specific coronal deformities, degenerative curves associated type 1-2 shapes, whereas idiopathic curves associated type 3-4.